2009
DOI: 10.1007/s00038-009-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of health-related quality of life on health service utilization in addition to socio-demographic and morbidity variables among primary care patients in China

Abstract: Health service utilization increased significantly with decreasing HRQOL, and the independent influence of HRQOL on health service utilization was smaller than that of socio-demographic and morbidity variables among primary care patients in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…This finding is consistent with the findings in previous reports on the impact of HRQOL on health service utilization in other study populations [13,23-25,44]. In the USA, Nelson and colleagues reported that physical functioning and mental health were two important predictors of both clinic consultation and hospitalization in patients with chronic diseases [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with the findings in previous reports on the impact of HRQOL on health service utilization in other study populations [13,23-25,44]. In the USA, Nelson and colleagues reported that physical functioning and mental health were two important predictors of both clinic consultation and hospitalization in patients with chronic diseases [23].…”
Section: Discussionsupporting
confidence: 92%
“…Dai M et al showed that females might have higher recent two-week morbidity (28.8% vs. 24.9%) and higher chronic disease morbidity (35.5% vs. 32.9%) than males [12]. Hence, optimizing the distribution of health service resources to improve the health of migrant female workers has become a priority for public health policy makers [13]. Rural-to-urban migrants in China have been studied in various aspects including socio-demographics, anthropology and management [14-17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several studies on the association between HRQOL and service utilization for Asian population (T. Chen & Li, 2009; C. L. K. Lam & Fong, 2002;Matsumura, 2000). A study by Matsumura in Japan found that subjects with Short Form-36 (SF-36) physical component summary (PCS) score below 40 were more likely to use outpatient services and to be hospitalized than those who had scores greater than 50 (Matsumura 2000).…”
Section: Hrqol and Service Utilizationmentioning
confidence: 99%
“…Numerous studies reported on the relationship between HRQOL and service utilization for Western and Asian populations (T. Chen & Li, 2009;Dominick & Ahern, 2004;Ethgen & Kahler, 2002; C. L. K. Lam & Fong, 2002;Matsumura, 2000;Nelson & McHorney, 1998;Parkerson & Gutman, 2000;Singh & Nelson, 2005), but no data were available for CHB patients. More studies are needed to explore the effect of HRQOL on service utilization in patients with CHB.…”
Section: Hrqol and Service Utilizationmentioning
confidence: 99%